2014
DOI: 10.1007/s00360-014-0860-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ectoine on heat-stressed Daphnia magna

Abstract: Ectoine (ECT) is an amino acid produced and accumulated by halophilic bacteria in stressful conditions in order to prevent the loss of water from the cell. There is a lack of knowledge on the effects of ECT in heat-stressed aquatic animals. The purpose of our study was to determine the influence of ECT on Daphnia magna subjected to heat stress with two temperature gradients: 1 and 0.1 °C/min in the range of 23–42 °C. Time to immobilisation, survival during recovery, swimming performance, heart rate, thoracic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 55 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…For instance, Daphnia dually exposed to cadmium and elevated temperature exhibited increased sensitivity 45 . Recorded responses of Daphnia to elevated temperatures include changes in swimming behavior, immobilization, and death 46 . The effect of SeMet on thermal stress has not yet been evaluated in Daphnia.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Daphnia dually exposed to cadmium and elevated temperature exhibited increased sensitivity 45 . Recorded responses of Daphnia to elevated temperatures include changes in swimming behavior, immobilization, and death 46 . The effect of SeMet on thermal stress has not yet been evaluated in Daphnia.…”
Section: Introductionmentioning
confidence: 99%
“…There are also results on effects induced by ECT in aquatic animals. Our previous studies revealed its low toxicity with the modulatory influence on heart activity, thoracic limb movement in Daphnia magna and protective effects in heat-stressed daphnids (Bownik et al, 2014;Bownik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms such as Marinococcus sp. ECT1 synthesize and accumulate intracellular ECT in response to osmotic stress during unfavourable environmental conditions, such as high temperature, salinity (Wei et al, 2011;Bownik et al, 2014). This amino acid protects bacterial cell membranes, enzymes and nucleic acids against dehydration (Galinski et al, 1985).…”
Section: Introductionmentioning
confidence: 99%